2001
DOI: 10.1016/s1074-7613(01)00242-4
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Is a Cellular Receptor Mediating Mycobacterial Heat Shock Protein 70 Stimulation of CC-Chemokines

Abstract: The 70 kDa mycobacterial heat shock protein (Mtb HSP70) stimulates mononuclear cells to release CC-chemokines. We now show that this function of Mtb HSP70, but not human HSP70, is dependent on the cell surface expression of CD40. Deletion of the CD40 cytoplasmic tail abolished, and CD40 antibody inhibited, Mtb HSP70 stimulation of CC-chemokine release. Mtb HSP70 stimulated THP1, KG1 cells, and monocyte-derived dendritic cells to produce RANTES. Specific binding of CD40-transfected HEK 293 cells to Mtb HSP70 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(215 citation statements)
references
References 51 publications
(2 reference statements)
9
203
1
Order By: Relevance
“…This would enable DC migration from the skin to the draining LN [23], and subsequently T cell priming in CD154 -/-but not CD40 -/-mice. The 70-kDa mycobacterial heat shock protein, present in CFA and able to bind CD40 [26], would be a candidate. Although this is an interesting possibility, our primary interests in this study lay in elucidating the effects of anti-CD40 versus anti-OX40 upon tolerance induction.…”
Section: Resultsmentioning
confidence: 99%
“…This would enable DC migration from the skin to the draining LN [23], and subsequently T cell priming in CD154 -/-but not CD40 -/-mice. The 70-kDa mycobacterial heat shock protein, present in CFA and able to bind CD40 [26], would be a candidate. Although this is an interesting possibility, our primary interests in this study lay in elucidating the effects of anti-CD40 versus anti-OX40 upon tolerance induction.…”
Section: Resultsmentioning
confidence: 99%
“…Whether other adjuvants will affect the expression of A3G needs to be examined. The overall results suggest that HSP70 might be used as an HIV-designer adjuvant in preventive and therapeutic vaccination, as HSP70 may inhibit both pre-entry transmission of HIV-1 into CD4 ϩ T cells or DC by generating CC chemokines (17,18), and postentry replication of HIV-1 by up-regulating A3G. Whereas the conventional concept of innate immunity has been that it lacks memory, this may not apply to all innate immune responses, as demonstrated recently with NK cells in delayed hypersensitivity (36).…”
Section: Discussionmentioning
confidence: 96%
“…We explored recent findings that 70-kDa heat shock protein (HSP)70 significantly inhibits HIV-1 infectivity of human CD4 ϩ T cells (K. Babaahmady, M. Singh, and T. Lehner, manuscript in preparation), and that it elicits chemokine and cytokine functions by engaging CCR5 and CD40 molecules (17)(18)(19). Indeed, we have found that in vitro stimulation of the cell surface CCR5 and CD40 molecules up-regulates A3G in CD4 ϩ T cells and DC.…”
Section: Stimulation Of Cell Surface Ccr5 and Cd40 Molecules By Theirmentioning
confidence: 99%
“…Studies also suggest that a small proportion of the hsp -peptide complex is loaded onto MHC class II, leading to the stimulation of CD4 þ cells (Matsutake and Srivastava, 1999). Other receptors, such as CD36 and CD40, were identified recently on APCs that can also interact with hsp's (Panjwani et al, 2000;Wang, 2001). These receptors, once activated, cause the secretion of nonspecific inflammatory cytokines such as tumour necrosis factors and interleukins (Ishii et al, 1999).…”
mentioning
confidence: 99%